Analysis of the Influence of Environmental Health Workers on Stunting Incidence - Husna, Nadiatul; Yulda, Apri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2024)
Environmental health workers play an important role in environmental factors that can affect health, such as clean water, sanitation, clean air, and waste management. This study aims to conduct a systematic review to investigate the impact of environmental health workers on stunting incidence. Full articles covering observational studies (cross-sectional, cohort, and case-control) published between 2012 and 2024 will be included. Article data collection was carried out by searching for articles in the Google Scholar, PubMed, and Science Direct search databases. Relevant data on the role of environmental health workers and stunting incidence will be extracted, presented systematically, and analyzed to identify patterns or relationships. This study showed there is a significant relationship between the role of environmental health workers and the incidence of stunting in children. It’s can be conclude that the influence of environmental health workers on the incidence of stunting. Keywords: Stunting, Environmental Health Officer, Prevention, Public Health